Fanning the Flames: Understanding Gang Involvement Among Philippine Prisoners - Lee, Sou (International journal of offender therapy and comparative criminology, 2019)
Utilizing intensive interview and observational data from inmates in one of the most overcrowded and underresourced jail in Metro Manila, Philippines, this study presents the first in-depth analysis of the factors associated with pangkat (prison gangs) and querna (nongang affiliation) membership. The results suggest that inmates join pangkats to ensure their safety and survival. In contrast, those who remain unaffiliated do so given their negative perceptions of the pangkat, sufficient access to social support, and desire to maintain their preprison identity. Furthermore, these major themes are situated within a modified general strain framework, which integrates traditional models of inmate adjustment, namely, deprivation, importation, and coping perspectives. In light of these findings, several implications for future research and policy are advanced, including the continued application of traditional criminological theories for understanding incarcerated populations and the formal integration of pangkats to jail administration given the lack of current reform strategies for addressing structural and institutional deficiencies.